2011
DOI: 10.3389/fnhum.2011.00001
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Sensitivity in Sensorimotor Control

Abstract: Recent advances in theoretical neuroscience suggest that motor control can be considered as a continuous decision-making process in which uncertainty plays a key role. Decision-makers can be risk-sensitive with respect to this uncertainty in that they may not only consider the average payoff of an outcome, but also consider the variability of the payoffs. Although such risk-sensitivity is a well-established phenomenon in psychology and economics, it has been much less studied in motor control. In fact, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
276
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(296 citation statements)
references
References 87 publications
19
276
1
Order By: Relevance
“…Therefore, choosing how to move an effector can also be considered as a decision-making problem [72]. While many previous studies have investigated the optimization of expected movement costs to describe behaviour, a number of recent studies has found risk-sensitive deviations from expected utility theory in sensorimotor control [73][74][75][76][77].…”
Section: (D) Application To Sensorimotor Controlmentioning
confidence: 99%
“…Therefore, choosing how to move an effector can also be considered as a decision-making problem [72]. While many previous studies have investigated the optimization of expected movement costs to describe behaviour, a number of recent studies has found risk-sensitive deviations from expected utility theory in sensorimotor control [73][74][75][76][77].…”
Section: (D) Application To Sensorimotor Controlmentioning
confidence: 99%
“…Recently, it was found that risk sensitivity is an important determinant in human sensorimotor behaviour [38]. Risksensitive decision-makers do not base their choices exclusively on the expectation value of a particular cost function, but they also consider higher-order moments of this cost function.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal control solution is given by the control law u * (·) that minimizes (3) constrained to dynamics (5) and (4). Due to the stochastic nature of (5), the cost to be optimized is a random variable.…”
Section: Problem Setting and Approachmentioning
confidence: 99%
“…The standard treatment in these settings is to minimize the expected value of the resulting stochastic cost. In contrast, human decisions under variability have been more accurately modeled by risk-sensitive decision-makers [4], which also considers cost variance. These results motivate us to consider high order cost statistics for control in robotic applications.…”
Section: Introductionmentioning
confidence: 99%